Evaluation of Arterial Functions and Carotid Intima Media Thickness in Children During Mid-Term Follow-Up After Kawasaki Disease - (:unkn) unknown (AVES, 2021)
Objective: Kawasaki disease (KD) is a multisystemic vasculitis of medium- and small-sized arteries. The involvement of the coronary arteries may lead to long-term cardiovascular sequelae. We studied the elasticity of the aorta and the common carotid artery (CCA), flow-mediated dilatation of the brachial artery, and carotid intima media thickness, as well biomarkers such as high-sensitivity C-reactive protein (hs-CRP) and elastin, as useful indicators of cardiovascular risk in patients, following KD. Methods: The study group consisted of 26 patients with a history of KD, and 26 healthy children. Echocardiography, and carotid and brachial ultrasound studies were performed. Plasma hsCRP and elastin levels were studied in both groups. Results: The stiffness indices (SI) obtained from the aortic arch, abdominal aorta, and the CCA were increased in the patients, compared to the controls. Distensibility was decreased at the sinus of Valsalva, the sinotubular junction, the aortic arch, and the ascending aorta, compared to the control group. Flow-mediated dilatation (FMD) was lower in the patients than in the controls. The age of the patients had a negative correlation to distensibility of the aortic arch and abdominal aorta, and a positive correlation to the stiffness of the aortic arch. Follow-up duration correlated positively to stiffness of the aortic arch. Carotid intima-media thickness (CIMT), serum hs-CRP, and elastin levels did not differ between the groups. Conclusion: Increased aortic and carotid stiffness and decreased aortic distensibility suggest impaired arterial functions following KD. Long-term follow-up and monitorization early in cardiovascular disease is needed.
Keywords: Arterial distensibility; arterial stiffness; cardiovascular risk; Kawasaki disease; long-term follow-up; ELASTIN-DERIVED PEPTIDES; LONG-TERM MANAGEMENT; C-REACTIVE PROTEIN; ENDOTHELIAL DYSFUNCTION; HEALTH-PROFESSIONALS; AORTIC STIFFNESS; ATHEROSCLEROSIS; ECHOCARDIOGRAPHY; ABNORMALITIES; PATHOGENESIS